Mest/Peg1 Is Essential for the Development and Maintenance of a SNc Neuronal Subset - Mesman, Simone; van Hooft, Johannes A.; Smidt, Marten P. (Frontiers in Molecular Neuroscience, 2017)
Mesodiencephalic dopaminergic (mdDA) neurons originate at the floor plate and floor plate-basal plate boundary of the midbrain ventricular zone. During development mdDA neurons are specified by a unique set of transcription factors and signaling cascades, to form the different molecular subsets of the mdDA neuronal population. In a time series micro-array study performed previously, mesoderm specific transcript (Mest) was found to be one of the most upregulated genes during early mdDA neuronal development. Here, we show that Mest transcript is expressed in the midbrain throughout development and becomes restricted to the substantia nigra (SNc) at late stages. In Mest KO animals mdDA neurons are progressively lost in the adult, mostly affecting the SNc, reflected by a 50% decrease of TH protein and DA release in the striatum and a reduction of climbing behavior. Analysis of Lrp6 KO embryos suggest a subtle opposite phenotype to the Mest KO, hinting towards the possibility that specific loss of mdDA neurons in Mest ablated animals could be due to affected WNT-signaling. Interestingly, the mdDA neuronal region affected by the loss of Mest remains relatively unaffected in Pitx3 mutants, suggesting that both genes are essential for the development and/or maintenance of different mdDA neuronal subsets within the SNc. Overall, the neuroanatomical and phenotypical consequences detected upon the loss of Mest, resemble the loss of SNc neurons and loss of movement control as seen in Parkinson's Disease (PD), suggesting that the Mest mouse model may be used as a model-system for PD.